1991
DOI: 10.1007/bf00497776
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of epithelial chloride channels by cytosol

Abstract: Chloride channels that have an intermediate conductance and are outwardly rectifying were studied by the patch-clamp technique in cell-excised membrane patches from respiratory epithelial cells in primary culture (REC) of normal and cystic fibrosis tissue, HT29 and T84 human colon carcinoma cells and placenta trophoblast cells (PTC). Chloride channels were immediately activated by the exposure of the cytosolic side of the patch to a Ringer-type solution, which lacked cytosolic components normally inhibiting ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…CFTR has been shown to regulate intracellular ceramide levels and to affect apoptosis by controlling glutathione transport. It is also entirely possible that the soluble cytosolic inhibitor of ORCC described earlier, is related to the metabolism of reactive oxygen species (17,27,28).…”
Section: Resultsmentioning
confidence: 98%
“…CFTR has been shown to regulate intracellular ceramide levels and to affect apoptosis by controlling glutathione transport. It is also entirely possible that the soluble cytosolic inhibitor of ORCC described earlier, is related to the metabolism of reactive oxygen species (17,27,28).…”
Section: Resultsmentioning
confidence: 98%
“…Third, C1C-6 and C1C-7 may be channels which are regulated in a complicated way which we have not yet understood. In fact, many patch-clamp studies have revealed chloride channels which can only be observed after patch-excision [33]. Fourth, these channels may reside in intracellular organelles, which are known to possess chloride channels as well [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The latter agrees with our present obser vations. On the other hand, it has been found that the outwardly rectifying Cl" channel can be activated by excising a membrane patch from its cell [5,19,33] which probably re flects detachment of a cytosolic inhibitor from the channel [ 18,20], This may also hold for the present experiments, since the rectify ing channel -in contrast to the bursting Cl" channel and the voltage-gated anion channel -was only observed in excised patches.…”
Section: Discussionmentioning
confidence: 48%